In the field a field experience manual for internship and service learning students - Hollis-Sawyer, Lisa A. 1963- (Cognella Academic Publishing, 2019)
"Provides readers with practical advice to help them prepare and conduct onsite field training in a variety of applied professions. It offers students weekly learning goals, case studies, informational asides, exercises, and discussion questions to engage them throughout their internship or service learning placement. The manual is appropriate for undergraduate or graduate programs and assumes the internship and service learning placements often occur outside of clinical mental health settings. The text is designed to function as a workbook that is easily adaptable to a student's unique training needs, allowing them to select the chapters that best align with their individual experiences and learning goals. It guides readers through the preplanning, planning, and onsite stages involved in a placement, encouraging them to critically consider the career development and academic learning involved throughout the process. Serving as an interactive guide that assists students in tracking the developmental nature of their own learning, In the Field helps readers make the most out of real-world experiences and onsite learning opportunities."--Page 4 of cover.